3m-3d 3m-2d -------- -- --------- Упростите выражение 2m-2d m-3d

0 голосов
151 просмотров

3m-3d 3m-2d
-------- -- --------- Упростите выражение
2m-2d m-3d


Алгебра (788 баллов) | 151 просмотров
Дан 1 ответ
0 голосов
Правильный ответ
\frac{3m - 3d}{2m-2d} - (- \frac{3m-2d}{m-3d} ) = \frac{3(m-d)}{2(m-d)} + \frac{3m-2d}{m-3d} = \frac{3}{2} +\frac{3m-2d}{m-3d} = \\ \\ 
= \frac{3(m-3d)+2(3m-2d)}{2(m-3d)} = \frac{3m-9d+6m-4d}{2(m-3d)} = \frac{9m-13d}{2m-6d}
Если  "--"  опечатка и выражение следует читать так:
\frac{3m - 3d}{2m-2d} - \frac{3m-2d}{m-3d} = \frac{3(m-d)}{2(m-d)} - \frac{3m-2d}{m-3d}= \frac{3}{2} -\frac{3m-2d}{m-3d}= \\ \\ 
= \frac{3*(m-3d) -2(3m-2d)}{2(m-3d)}= \frac{3m-9d-6m+4d}{2(m-3d)} = \frac{5d-3m}{2m-6d}
(271k баллов)